Towards a systematic approach to integrate usage and decision knowledge in continuous software engineering - Johanßen, Jan Ole; Kleebaum, Anja; Paech, Barbara (Proceedings of the 2nd Workshop on Continuous Software Engineering, 2017)
Continuous software engineering (CSE) employs activities such as continuous integration and continuous delivery to support software evolution. Another aspect of software evolution is knowledge management. There are two important knowledge types: usage knowledge derives from explicit and implicit user feedback and helps to understand how users utilize software. Decision knowledge encompasses decisions and their rationale on all aspects of the software lifecycle. Both knowledge types represent important information sources for developers to improve the CSE activities and the software product. We envision an integration of usage and decision knowledge in the CSE lifecycle. This extension consists of a monitoring and feedback component for user understanding as well as a knowledge repository and dashboard component for knowledge visualization and analysis. Usage and decision knowledge introduce challenges when integrating them in CSE. In this paper, we present our vision and detail the challenges.
Gesehen am 20.07.2018
Keywords: Konferenzschrift